2005
DOI: 10.1159/000084749
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of the Predisposing Factors in Erythema toxicum neonatorum

Abstract: Background: Erythema toxicum neonatorum (ETN) is a very common disease, but its predisposing factors are still unknown. Objective: To determine the predisposing factors of ETN. Methods: Seven hundred and eighty-three neonates born in the same hospital during the same period were investigated, and the factors predisposing to ETN were evaluated in a case-control study. Results: (1) The incidence of ETN is about 43.68%, and it is significantly higher in males than in females (p < 0.001). (2) Term birth (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 5 publications
9
33
4
4
Order By: Relevance
“…Some studies [10,11] found a significant correlation between the frequency of the lesion and vaginal delivery, whereas another [6] revealed a higher incidence in neonates born by cesarean section. Liu et al [10] and Sadana et al [9] observed an association with primiparity, whereas others [6,7] detected a higher frequency in cases of multiparity. The data relating to the frequency according to gender were also contradictory.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies [10,11] found a significant correlation between the frequency of the lesion and vaginal delivery, whereas another [6] revealed a higher incidence in neonates born by cesarean section. Liu et al [10] and Sadana et al [9] observed an association with primiparity, whereas others [6,7] detected a higher frequency in cases of multiparity. The data relating to the frequency according to gender were also contradictory.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11] Mostly, these studies included the examination of 500-1000 neonates, and were conducted in Asia; [1][2][3][5][6][7][8][9] few studies on neonatal skin manifestations have been reported in Europe. [4] Some reports detected all the skin manifestations found, whereas others examined only some specifi c condition, such as erythema toxicum neonatorum (ETN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published study, several predisposing factors for ETN where identified such as female sex, term birth, first-pregnancy birth, birth season (summer and autumn), and vaginal delivery. 4 The skin lesions of erythema toxicum ( Figure 1) are asymptomatic red macules, papules, pustules or wheals that can affect any area of the body and most commonly present after 24 to 72 hours of life, but may begin from birth to 2 weeks of age. 5 Since ETN is a short lasting dermatosis, prevalence reports differ according to the time of life the neonate is examined.…”
Section: Noninfectious Neonatal Pustular Eruptions 1 Erythema Toxmentioning
confidence: 99%
“…This is especially true for the very preterm neonates (< 32 weeks), but moderate (32-33 weeks) and late (34)(35)(36) weeks) preterm neonates may also have worse neurodevelopmental and educational outcomes as compared with neonates born after at least 37 weeks of gestation. been numerous thorough studies on adaptation and disorders of many organs and organ systems, neonatal dermatology is a much less well studied and reviewed field of medicine.…”
Section: Discussionmentioning
confidence: 99%